Cancer of unknown primary - Krämer, Alwin; Löffler, Harald (Springer, 2016)
Introduction.- Epidemiology, risk factors and survival in CUP: pointers to disease mechanisms -- Biologic features of CUP -- Prognostic factors and their role in the management of CUP -- Diagnostic work-up of CUP – an approach to current recommendations and underlying evidence -- The radiologist’s approach to CUP -- Cancer of unknown primary: the pathologist’s approach -- Treatment of disseminated CUP -- Concepts of radiotherapy in cancer of unknown primary -- Favorable subsets of CUP -- Novel Diagnostic and Therapeutic Strategies in the Management of Patients with Cancers of Unknown Primary Site -- Future directions.
Includes bibliographical references at the end of each chapters